Farming within a dual legal land system: An argument for emancipatory food systems planning in Accra, Ghana. (March 2020) - Frimpong Boamah, Emmanuel; Sumberg, James; Raja, Samina
Highlights: Ghana's dual legal land systems affect smallholder farmers in cities. The dual land rules are structured by the interplay of power, knowledge, subjectivity, and space. Smallholder farmers navigate the dual land rules through compliance, opposition, and adaptation. Emancipatory urban planning can help address systemic inequality facing smallholder farmers in their access to land. Abstract: Contestation over land is a central element of urban food systems. This paper examines how Ghana's dual legal land system affects urban farmers. Situated within the "emancipatory planning" discourse, the paper investigates how farmers navigate customary and statutory land rules using tactics that include compliance, opposition and adaptation. Based on field work conducted in urban and peri-urban areas of Accra, the study demonstrates that farmers access land by working around, outside, and within the rules of the dual legal land system. The landowners on whom urban farmers depend also both comply with and violate these same rules. This system perpetuates inequities. Food systems policy and planning must address the structural and systemic inequities that are reinforced by the rules of the land game. The paper concludes with some reflections on how local and national policy and planning can do a better job in supporting urban food production in contexts characterized by complex, dual legal land systems.